THE LAW POLITICS IN THE REFORMULATION OF INTERFAITH MARRIAGE IN INDONESIA - Teti Hadiati (Fakultas Syariah UINFAS Bengkulu, 2020)
The problems examined in this study is wast are interfaith marriages in accordance with the philosophical values of Indonesian marriage law? and why is the validity of interfaith marriages still being disputed in Indonesian marriage law? Related to the principle of continuing legal conditions and public order, the implementation of registration marriage by registration is a form of acceptance of interfaith marriages and the community has accepted the phenomenon of interfaith marriages as a natural reality and is considered to be true. This research is normative legal research and quantitative sociological legal research. The study methodology is analyzed based on the principle of public order, law smuggling, and continuation of the legal situation or rights that have been obtained. From this research, it was concluded that interfaith marriages were considered incompatible with the philosophical values of Indonesian Marriage law which were based on religious law, and could injure the long struggle history of Indonesian marriage law legislation under the principle of public order. Therefore, the registrations carried out by the civil registry office are not authoritative, but merely administrative.